Ecological Knowledge and Management of Fauna Among the Mexicatl of the Sierra Negra, México: An Interpretive Approach - Zarazúa-Carbajal, Mariana; Chávez-Gutiérrez, Michelle; Peña-Mondragón, Juan Luis; Casas, Alejandro (Frontiers in Ecology and Evolution, 2022)
Generally motivated by the relevance of animals in human subsistence, the management of fauna has taken different shapes throughout the world. This study aims to analyse a typology of management forms, exploring their relationship with the motivation to maintain coexistence and use of fauna and mitigate negative human-fauna interactions by the Mexicatl (Nahua) people in Central Mexico. We generally expected to find a broad spectrum of management types in a gradient of interactions intensity. This is because we hypothesised that the more meaningful these interactions due to the magnitude of benefit or damage, philias, or phobias among other positive or negative perceptions, and ecological aspects and management viability, the more actions and practices might be motivated to maintain or mitigate them. We conducted a qualitative research based on interpretivist approaches, mixing qualitative and quantitative analyses, to register the Mexicatl names of fauna present in the area and recognised by locals and to analyse the influence of local ecological knowledge (LEK) and natural history as perceived by people on the use, conflicts, and management practices regarding local fauna. In order to gather such information, in 2018 and 2019 we generated 356 free lists of fauna and 20 sessions of group interviews about the presence of animals in the area, the Mexicatl name, information on distribution, diet, use, management, and other facts. We used visual stimuli with children and young people from schools of basic and intermediate levels in five rural communities and the municipal head of Coyomeapan, Puebla. We also generated free lists and in-depth interviews with 18 persons older than 16 years. People recognised 114 animal items, the most salient being 11 domestic and 14 wild animals including deer, medium and small mammals, snakes, and birds. For both domestic and wild fauna, people reported 18 use categories and three types of damage (crop losses, predation of domestic animals, and damages to health). LEK interacted with traditional celebrations, religious beliefs, land tenure, and migration to define preferences and management types of fauna. Bushmeat demand, especially for Mazama temama and Cuniculus paca, was related to a perception of healthy nutrition properties. Management actions included husbandry of domestic animals, extraction of wild animals for supply, or to avoid damages, captivity, tolerance to damage, protection of seeds and domestic animals threatened by wild fauna, regulations for extraction of wild fauna, and agreements to prevent conflicts. Mixed quantitative and qualitative approaches allowed the interpretation of the human-fauna interactions related to subsistence, coexistence, and the high relevance of LEK, perceptions, religious beliefs, ecosystem, socio-demographic factors, and animal behaviour and habits, which are crucial factors that influence the shaping of management practices. Local management strategies of fauna were diverse and contribute to biocultural conservation and theoretical construction on domestication.